Konsep dan Implementasi Manajemen Pendidikan Islam dan Ekonomi Syariah di Asia Tenggara - Musta'an Musta'an (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this study is to understand the concepts and implementation of Islamic education and Islamic economic management in Southeast Asia, where the object of this research is the management of Islamic education and Islamic economics in Indonesia and Malaysia. The research method uses the literature study method using a historical approach. By using these methods and approaches the concepts and implementation of Islamic education and Islamic economic management in Southeast Asia (in Indonesia and Malaysia) are expected to build a clear picture through various theories that have existed and developed previously. The results show that there are various similarities between the concepts and implementation of Islamic education management and Islamic economics in Indonesia and Malaysia, which are geographically close together so that they experience the same historical phases caused by the stages of the period of international civilization. Another thing that causes similarities is that the two countries are both in the development of sharia economics which continues to grow, although until now the development of the sharia economy in Malaysia, especially the banking industry has developed much more rapidly than in Indonesia.